Management Risk in Business Defense : Administrative Studies Business to Security Supply - Arief Prayitno (Sean Institute, 2024)
Defense industry face challenge complex in manage risk, especially related security supply that affects stability operational and readiness strategic. Research This aiming For analyze management risk in business defense with focus on the strategy implemented For guard security supply. Using approach administration business, study This explore factors risk main, including risk financial, operational, technical, and regulatory, as well as the impact to sustainability chain supply.Research This use method qualitative with studies case with technique data collection through interview in-depth, survey, and analysis document industry defense. Research results This show that management effective risk in chain supply industry defense play a role important in guard readiness operational and sustainability production equipment military. Diversification Supplier proven capable reduce dependence on sources certain, while utilization technology such as big data, intelligence artificial intelligence (AI), and the Internet of Things (IoT) enable detection early to potential disturbance chain supply. In addition, strengthening regulation, improvement management inventory and stock reserves, as well as investment in development production domestically become step strategic For increase resilience chain supply and independence industry defense. In overall, research This confirm that implementation of management strategies systematic risk can minimize impact disturbance supply, increase efficiency operational, as well as strengthen stability and power competition industry defense national in face global challenges.